Preliminary Outcomes from PrEP Well: A Community-led, Multicomponent HIV Prevention Strategy Implemented in a Transgender Community Health Center. - Storholm, Erik D.; Nacht, Carrie L.; Opalo, Chloe; Flynn, Risa; Murtaugh, Kimberly Ling; Marroquin, Mariana; Baumgardner, Mika; Dopp, Alex R. (Journal of Community Health, 2025)
Transgender and nonbinary (TGNB) individuals are disproportionately impacted by HIV, particularly those who identify as racial/ethnic minorities and those who are socioeconomically disadvantaged. Pre-exposure prophylaxis (PrEP) is a highly effective medication to prevent HIV infection, but many TGNB individuals encounter barriers to PrEP uptake and adherence that limit fully realized preventive benefits. We developed PrEP Well, a multicomponent community-led program, to scale and sustain comprehensive PrEP services from a TGNB-led community organization that provides gender-affirming healthcare and social services. We used implementation science frameworks to evaluate initial program outcomes and contextual influences on program implementation. Preliminary data from August 2022 through January 2024 showed promising implementation and effectiveness outcomes. During that time, 113 primarily low-resourced TGNB clients were educated about PrEP and received an HIV test, of whom 60 (53%) attended a visit with a provider and received a PrEP prescription. At 30-day follow-up, urinalysis confirmed uptake of PrEP among 50 (83%) of the clients prescribed PrEP. At 90-day follow-up, 43 (72%) demonstrated continued use of PrEP and 40 (67%) showed protective levels of PrEP adherence. Qualitative interviews and surveys indicated that clients, staff, and leadership viewed the PrEP Well program as highly acceptable, feasible, and sustainable (including willingness to address persistent implementation barriers). Referral patterns and rates of PrEP uptake suggested increasing integration of PrEP Well into the TGNB community center over time. The PrEP Well program demonstrates the potential for TGNB communities to address HIV inequities by integrating community-led HIV prevention services with gender-affirming healthcare in TGNB-specific health centers.